Morphological and biochemical mechanisms of resistance against powdery mildew (Golovinomyces cichoraceaarun) of sunflower (Helianthus annuus L.): Morphological and biochemical mechanisms of resistance against powdery mildew (Golovinomyces cichoraceaarun) of sunflower (Helianthus annuus L.) - V N TOPROPE; G D MATSAGAR (Journal of Oilseeds Research, 2020)
Eighteen hybrids and two checks of sunflower were evaluated for their morphological and biochemical traits imparting tolerance/resistance to powdery mildew during rabi, 2015-16. The results revealed that sunflower hybrids viz., LSFH-2026, LSFH-216, LSFH-3008 and LSFH-1225 exhibited moderately resistant to moderately susceptible reaction to powdery mildew. Moderately resistant hybrids exhibited least frequency and size of stomata and higher trichome density. The biochemical traits revealed that these hybrids had higher amounts of total phenols, total sugars and chlorophyll in healthy leaves. The rate of reduction of total phenols, total sugars and chlorophyll content was minimum in these three hybrids as compared to susceptible checks, after infection of powdery mildewpathogen